The low‐recombining pericentromeric region of barley restricts gene diversity and evolution but not gene expression. (5th August 2014) - Baker, Katie; Bayer, Micha; Cook, Nicola; Dreißig, Steven; Dhillon, Taniya; Russell, Joanne; Hedley, Pete E; Morris, Jenny; Ramsay, Luke; Colas, Isabelle; Waugh, Robbie; Steffenson, Brian; et al.
Summary The low‐recombining pericentromeric region of the barley genome contains roughly a quarter of the genes of the species, embedded in low‐recombining DNA that is rich in repeats and repressive chromatin signatures. We have investigated the effects of pericentromeric region residency upon the expression, diversity and evolution of these genes. We observe no significant difference in average transcript level or developmental RNA specificity between the barley pericentromeric region and the rest of the genome. In contrast, all of the evolutionary parameters studied here show evidence of compromised gene evolution in this region. First, genes within the pericentromeric region of wild barley show reduced diversity and significantly weakened purifying selection compared with the rest of the genome. Second, gene duplicates (ohnolog pairs) derived from the cereal whole‐genome duplication event ca. 60MYa have been completely eliminated from the barley pericentromeric region. Third, local gene duplication in the pericentromeric region is reduced by 29% relative to the rest of the genome. Thus, the pericentromeric region of barley is a permissive environment for gene expression but has restricted gene evolution in a sizeable fraction of barley's genes.